Reproducibility, stability, and biological variability of thrombin generation using calibrated automated thrombography in healthy dogs. (26th March 2018) - Cuq, Benoît; Blois, Shauna L.; Wood, R. Darren; Monteith, Gabrielle; Abrams‐Ogg, Anthony C.; Bédard, Christian; Wood, Geoffrey A.
Abstract : Background: Thrombin plays a central role in hemostasis and thrombosis. Calibrated automated thrombography (CAT), a thrombin generation assay, may be a useful test for hemostatic disorders in dogs. Objectives: To describe CAT results in a group of healthy dogs, and assess preanalytical variables and biological variability. Animals: Forty healthy dogs were enrolled. Methods: Lag time ( Lag ), time to peak ( ttpeak ), peak thrombin generation ( peak ), and endogenous thrombin potential ( ETP ) were measured. Direct jugular venipuncture and winged‐needle catheter‐assisted saphenous venipuncture were used to collect samples from each dog, and results were compared between methods. Sample stability at −80°C was assessed over 12 months in a subset of samples. Biological variability of CAT was assessed via nested ANOVA using samples obtained weekly from a subset of 9 dogs for 4 consecutive weeks. Results: Samples for CAT were stable at −80°C over 12 months of storage. Samples collected via winged‐needle catheter venipuncture showed poor repeatability compared to direct venipuncture samples; there was also poor agreement between the 2 sampling methods. Intra‐individual variability of CAT parameters was below 25%; inter‐individual variability ranged from 36.9% to 78.5%. Conclusions: Measurement of thrombin generation using CAT appears to be repeatable in healthy dogs, and samples are stable for at least 12 months when stored at −80°C. Direct venipuncture sampling is recommended for CAT. Low indices of individuality suggest that subject‐based reference intervals are more suitable when interpreting CAT results.